Scientific Basis in Learning: Psychology, Communication, and Management - Nur Ali Yasin; Hidayati, Arini; Nurlailin, Wiwik (Educational Journal of Learning Technology, 2025)
This article explores the scientific foundations of learning from educational psychology, communication, and classroom management perspectives. A qualitative-descriptive library research method identifies key issues such as limited teacher understanding of student development and weak communication skills. The findings emphasize the importance of psychological insight, empathetic communication, and effective management in creating adaptive, humanistic learning. The study proposes strategies including differentiated instruction, empathy-based communication, and innovative classroom practices. Integrating these foundations is crucial to shaping professional and responsive educators facing modern educational challenges.